(2y-1)(2y+1)=

Simple and best practice solution for (2y-1)(2y+1)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (2y-1)(2y+1)= equation:


Simplifying
(2y + -1)(2y + 1) = 0

Reorder the terms:
(-1 + 2y)(2y + 1) = 0

Reorder the terms:
(-1 + 2y)(1 + 2y) = 0

Multiply (-1 + 2y) * (1 + 2y)
(-1(1 + 2y) + 2y * (1 + 2y)) = 0
((1 * -1 + 2y * -1) + 2y * (1 + 2y)) = 0
((-1 + -2y) + 2y * (1 + 2y)) = 0
(-1 + -2y + (1 * 2y + 2y * 2y)) = 0
(-1 + -2y + (2y + 4y2)) = 0

Combine like terms: -2y + 2y = 0
(-1 + 0 + 4y2) = 0
(-1 + 4y2) = 0

Solving
-1 + 4y2 = 0

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '1' to each side of the equation.
-1 + 1 + 4y2 = 0 + 1

Combine like terms: -1 + 1 = 0
0 + 4y2 = 0 + 1
4y2 = 0 + 1

Combine like terms: 0 + 1 = 1
4y2 = 1

Divide each side by '4'.
y2 = 0.25

Simplifying
y2 = 0.25

Take the square root of each side:
y = {-0.5, 0.5}

See similar equations:

| 4x+-3=2x+-12 | | -3y+3-2y=-8+2y | | -1+2=12 | | 5x^2(4x^3+10x)=0 | | .0002x^2-.316x+135.9=0 | | 4(x-2)(x+3)= | | X-a=b | | 14x=-10 | | -6.2+11.4=25 | | 5x(2x-1)-14=2x(5x+6)+3 | | 12x^2-36x-21=0 | | 9(x-3)=2(5x-1) | | 3-6y=12+18y | | 125=(4r+2)+(5r-12) | | 1r+-3=-8 | | -3(t-1)+9t=4t-1 | | 7d+7=14 | | -4.9t^2+6t+.5=0 | | p^11+9=6 | | 8x+4=-3 | | 6.2-1.4=3.87 | | 5x+2y-12=x | | 8(4n-4)=-4(4-6n) | | -2x^2+2x+2=0 | | 8a+9=6a-7 | | 5-3x=-15 | | 8-3(4x-1)=7 | | 2x^2+11x-3=0 | | -9x^2+8y=6equation | | 5p+2-3p=8+5u-11 | | 4(3+7)/(6+4)-9= | | 9x-(4x+7)=28 |

Equations solver categories